HUBUNGAN MEMBACA BERITA DENGAN KEMAMPUAN MENULIS PARAGRAF EKSPOSISI SISWA KELAS X SMA NEGERI 1 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Priana, Dwivika Septi; Laila, Aruna; Andheska, Harry (Pendidikan Bahasa Indonesia, 2014)
The background of this research are the problems faced by students of class X SMA N 1 Tarusan in the ability to write a faragraph of exposition is still low, which is the main dificulty for students in writing is to find ideas and develop ideas. In writing paragraphs of exposition students are required to readÂ  the news read with unfamiliar students will be helped to expose a knowledge or information. This study aims to (1) describe the news reading class X SMA N 1 Tarusan, (2) describe the ability to write a paragraph of exposition class X SMA N 1 Tarusan, (3) analyze the relationship reading the news with the ability to write a paragraph of exposition class X SMA N 1 Tarusan. Types of research used in this study is quantitative descriptive method. The sampling tecnique used in this study is random sampling, which is sampling besed on the population of the number of students every class. The study population class X SMA N 1 Tarusan with the sampling amounted to 64 people. File were obfained through two kinds of tests are objektive tests and performance tests. Objektive test is used collect file while the reasoning knowledge of performance test are used to gather file of exposition paragraph writing skills. The results showed that the relationship reading the news with the ability to write a paragraph of exposition class X SMA N 1 Tarusan there is a significant positive relationship. Based on file analysis and discussion, the avarage count obtained news reading class X SMA N 1 Tarusan are more than enougth in qualitying (68,67) in the range of 66-75%. Subtantial realitionship betwen the two variabels with rhitungobtained count of 0,34 wich is the result of reading the news correation with the ability to write a paragraph of exposition class X SMA N 1 Tarusan and hypotesis testing result prove that thitung > ttabelis (2,84>1,67).